2017
DOI: 10.1055/s-0043-102402
|View full text |Cite
|
Sign up to set email alerts
|

Utilization trends in inpatient endoscopic retrograde cholangiopancreatography (ERCP): A cross-sectional US experience

Abstract: Study aims The goal of our study was to determine the current trends for inpatient utilization for endoscopic retrograde cholangiopancreatography (ERCP) and its economic impact in the United States between 2002 and 2013. Patients and methods A Nationwide Inpatient Sample from 2002 through 2013 was examined. We identified ERCPs using International Classification of Diseases (ICD-9) codes; Procedure codes 51.10, 51.11, 52.13, 51.14, 51.15, 52.14 and 52.92 for diagnostic and 51.84, 51.86, 52.97 were studied. Rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 17 publications
(17 reference statements)
2
35
1
2
Order By: Relevance
“…Last, there was a downtrend in the number of ERCPs performed over our study and especially in 2013. However, this trend has been observed in prior studies evaluating the trend of ERCP in the US …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Last, there was a downtrend in the number of ERCPs performed over our study and especially in 2013. However, this trend has been observed in prior studies evaluating the trend of ERCP in the US …”
Section: Discussionmentioning
confidence: 74%
“…However, this trend has been observed in prior studies evaluating the trend of ERCP in the US. 24,25 To the best of our knowledge, this is the first populationbased study to examine variations in access to ERCP across the United States. The findings suggest that utilization of ERCP varies according to race/ethnicity and geographic location in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that in the United States, the frequency of therapeutic ERCP was 5.9 times higher than that of diagnostic ERCP in 2013, which is similar to the findings of this study. 17 Among the 10 administrative divisions, Seoul and Jeonbuk had a much greater adjusted numbers of patients per 100,000 than other divisions. In case of Seoul, it can be guessed that many patients from other divisions were treated in Seoul, and there were many tertiary or general hospitals.…”
Section: Discussionmentioning
confidence: 96%
“…With respect to the ratio of therapeutic to diagnostic ERCP, the average annual number of therapeutic ERCPs performed was far higher than that of diagnostic ERCPs, which was also seen in other studies. [2][3][4]17,18 Moreover, therapeutic procedures continuously increased throughout the 5-year period; however, there was no increase in the number of diagnostic ERCPs performed. Nonetheless, the frequency of diagnostic ERCP may still seem very high, with about 7,000 diagnostic ERCPs performed per year.…”
Section: Discussionmentioning
confidence: 99%
“…In the current issue of Endoscopy International Open, Ahmed, et al discuss trends for utilization of endoscopic retrograde cholangio-pancreatography in the United States over the years 2002 to 2013 1. Not surprising has been a shift from diagnostic to therapeutic ERCP and an accompanying fall in total procedures in the years between 2011 and 2013.…”
mentioning
confidence: 99%